Let
x---------> the length of the first piece
y---------> the length of the second piece
z---------> the length of the third piece
we know that
x+y+z=72 -------> equation 1
y=x+6 -----> solve for x
x=y-6 -------> equation 2
z=6+y -------> equation 3
substitute equation 2 and equation 3 in equation 1
[y-6]+y+[6+y]=72
3y=72
y=(72/3)=24 in
Find the value of x
x=y-6 -------> equation 2
x=24-6=18 in
Find the value of z
z=6+y -------> equation 3
z=6+24=30 in
therefore
the answer is
the length of the first piece is 18 in
the length of the second piece 24 in
the length of the third piece is 30 in